2013
DOI: 10.4049/jimmunol.1203085
|View full text |Cite
|
Sign up to set email alerts
|

Human T Cells Engineered To Express a Programmed Death 1/28 Costimulatory Retargeting Molecule Display Enhanced Antitumor Activity

Abstract: Adoptive transfer of T cells genetically modified to express cancer-specific receptors can mediate impressive tumor regression in terminally ill patients. However, T cell function and persistence over time could be hampered by the activation of inhibitory costimulatory pathways, such as programmed death 1 (PD1)/programmed death ligand 1, leading to T cell exhaustion and providing tumor cells with an escape mechanism from immunosurveillance. In addition, the lack of positive costimulation at the tumor site can … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
83
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 92 publications
(84 citation statements)
references
References 52 publications
1
83
0
Order By: Relevance
“…PD-1:28 engineering invigorated TILs that were functionally disabled in human RCC environments. These TILs recovered Th1-cytokine secretion without unleashing Th2 or IL10 programs presumably based on restoration of ERK and AKT pathways as shown in our in vitro coculture system and previous work using similar receptors (25,26). PD-1:28 ameliorated T-cell inhibition that involved native PD-1/PD-L1 interactions and induced the costimulatory signaling pathway.…”
Section: Discussionsupporting
confidence: 62%
See 2 more Smart Citations
“…PD-1:28 engineering invigorated TILs that were functionally disabled in human RCC environments. These TILs recovered Th1-cytokine secretion without unleashing Th2 or IL10 programs presumably based on restoration of ERK and AKT pathways as shown in our in vitro coculture system and previous work using similar receptors (25,26). PD-1:28 ameliorated T-cell inhibition that involved native PD-1/PD-L1 interactions and induced the costimulatory signaling pathway.…”
Section: Discussionsupporting
confidence: 62%
“…Harnessing them for the antitumor response would enlarge and enrich the spectrum of T cells for ATT. As previous data have shown that PD-1:28 receptors can improve TCR-and chimeric antigen receptor (CAR)-engineered T cells (25,26,38,39), we engineered low-avidity T cells with a PD-1:28 chimeric signaling receptor to explore whether their functional activity could be enhanced allowing their inclusion in a library of TCRs for ATT. We show that PD-1:28 chimeric receptor can be stably expressed on the surface of human T cells.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It was suggested the role in CAR signal transduction via TM domain that comes into interaction with different membrane co-receptors [114]. We also recently showed that CD28 TM domain maybe superior to the native one in certain types of chimeric receptors [105,115]. Still, more research is required to obtain a more reliable understanding of TM domain impact on CAR stability and function [116].…”
Section: Car Basic Structural Principal and Determinant Of Functionmentioning
confidence: 99%
“…CTLA-4/CD28 chimera maximized T-cell antitumor function in preclinical lymphoma and melanoma syngenic mouse models (38). T cells modified to express PD-1/CD28 chimeric molecules exhibited enhanced cytokine secretion, upregulation of activation markers, and improved proliferation upon coculture with tumor cells in vitro when compared with control cells, and superior in vivo antitumor function in two xenograft models of human melanoma tumors (39). These innovative chimeric proteins can be cotransduced with tumor-targeting CARs to combine tumor T-cell specificity, T-cell activation, and abrogation of checkpoint inhibition in a single genetically modified T-cell.…”
Section: Discussionmentioning
confidence: 99%